Reinforcements - Grant, Heidi (Harvard Business Review Press, 2018)
Imagine walking up to a stranger on the subway and asking them for their seat. What about asking a random person on the street if you could borrow their phone? If the idea makes you squeamish, you're not alone--social psychologists have found that doing these very things makes most of us almost unbearably uncomfortable. But here's the funny thing: even though we hate to ask for help, most people are wired to be helpful. And that's a good thing, because every day in the modern, uber-collaborative workplace, we all need to know when and how to call in the cavalry. However, asking people for help isn't intuitive; in fact, a lot of our instincts are wrong. As a result, we do a poor job of calling in the reinforcements we need, leaving confused or even offended colleagues in our wake. This pragmatic book explains how to get it right. With humor, insight, and engaging storytelling, Heidi Grant, PhD, describes how to elicit helpful behavior from your friends, family, and colleagues--in a way that leaves them feeling genuinely happy to lend a hand. Whether you're a first-time manager or a seasoned leader, getting people to pitch in is what leadership is. Fortunately, people have a natural instinct to help other human beings; you just need to know how to channel this urge into what it is you specifically need them to do. It's not manipulation. It's just management.